GAS Detector sensor of Biology System - Majali, Alaa Abdul-Hussein (Indonesian Journal on Health Science and Medicine, 2025)
Background: We discuss advances in bioimaging technologies and gas-phase molecular biosensors. These technologies selectively detect volatile biochemicals using the high resolution of biorecognition elements. Methods: Gas-phase biosensors employ enzymes as recognition components. These devices produce luminescent molecules and other detectable products through redox reactions of volatile biochemicals. Results: Biosensors utilizing other biorecognition elements, including molecularly imprinted polymers, olfactory receptors, cells, and antibodies, are demonstrated. When used in combination with optical, electrochemical, and liquid biorecognition components, biosensors exhibit a unique and powerful property: they are insensitive to humidity. This important feature enables biosensors to detect volatile biochemicals in the breath and other humid environments. The use of imaging technologies and improvements in recording the spatiotemporal distribution of volatile biochemicals with improved continuity are also discussed. Aims: These new techniques are expected to be used to monitor environmental volatile biochemicals with high resolution and identify the hitherto undiscovered relationship between health and spatial and temporal fluctuations in volatile biochemicals in skin or breath gas. Highlights: A gas detector sensor is used for the biology system to detect the presence of certain gases in the surrounding environment. Used as part of a safety system to detect leaks of hazardous or flammable gases. These sensors work by sensing changes in the concentration of gases in the air and alerting when a certain level is exceeded. Keywords: Bioimaging Technologies, Gas-Phase Biosensors, Volatile Biochemicals, Biorecognition Elements, Humidity Insensitivity